Targeting of hyperlipid-producing senescent synovial fibroblasts to ameliorate cartilage degeneration - Jiajie Hu; Dongsheng Yu; Jiasheng Wang; Peng Guo; Mingming Chen; Dongmei Wu; Youzhi Cai; Yixuan Wang; Junfeng Ji; Xudong Yao; Hongwei Ouyang (Proceedings of the National Academy of Sciences, 2025)
Osteoarthritis (OA) is one of the most common causes of physical disability among older people and its incidence increases with age. Removal of the senescent cells (SNCs) delays OA pathologies, but little is known about the heterogeneity of SNCs and their roles in OA pathogenesis. Here, we identify a subpopulation of senescent synovial cells and proposed a molecular mechanism governing pathogenic synovium-cartilage crosstalk in OA progression. Using single-cell RNA sequencing and synovial organoids, we demonstrate that RCAN1 + IL1α + senescent synovial fibroblasts, predominantly located in the lining layer of human OA synovium, exhibit proinflammatory phenotype, mitochondrial dysfunction, and promote cartilage degeneration. Mechanistically, RCAN1 stabilizes ATF4 mRNA and mediates saturated fatty acids (SFA) secretion from synovial fibroblasts, which could promote chondrocyte senescence and cartilage matrix degradation. Synovium-targeted delivery of anti-RCAN1 siRNA significantly ameliorated posttraumatic OA development in mice, reducing of SNC accumulation in synovium and increasing cartilage regeneration. Coculture experiments with human OA cartilage explants and synovial organoids confirm that RCAN1 silencing in synovial fibroblasts suppressess chondrocyte senescence and cartilage degradation. Our findings reveal a prodegenerative interaction between RCAN1 + IL1α + senescent synovial fibroblasts and chondrocytes mediated by secreted lipid in OA progression. Targeted RCAN1 knockdown in senescent synovium could be a new treatment strategy for restoring the joint homeostasis.